Sewing time: weaving a Nagô archive - Amaral, Diego Granja do (2021)
Upon a brief comment on the notion of archive fever in Derrida ([1995] 2001), this paper proposes a reinterpretation of the issue concerning the archive which builds upon the notion of Arkhé nagô (SODRÉ, 2017) based on the work of Rosana Paulino. As a central argument, I contend for the necessity of producing archives as healing spaces and areas for creative emergence of memory. Bearing this in mind, I propose the notion of nagô archive, a proposition that builds upon an analysis of the Black Lives Matter protests in Bristol and the works of Rosana Paulino, the latter being the central focus of the analysis. The main goal is to discuss the issue of the archive within the context of contemporary Brazil, hence from a non-Eurocentric point of view.